2019
DOI: 10.1109/lra.2019.2935351
|View full text |Cite
|
Sign up to set email alerts
|

Spine-Inspired Continuum Soft Exoskeleton for Stoop Lifting Assistance

Abstract: Back injuries are the most prevalent work-related musculoskeletal disorders and represent a major cause of disability. Although innovations in wearable robots aim to alleviate this hazard, the majority of existing exoskeletons are obtrusive because the rigid linkage design limits natural movement, thus causing ergonomic risk. Moreover, these existing systems are typically only suitable for one type of movement assistance, not ubiquitous for a wide variety of activities. To fill in this gap, this paper presents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 33 publications
3
36
0
Order By: Relevance
“…One review reported seven passive back exoskeletons (de Looze et al, 2016), and several designs have been published since then (Lamers et al, 2017;Baltrusch et al, 2020). Similarly, there have been many active back exoskeletons; some recent examples include Huysamen et al (2018), Ko et al (2018), Toxiri et al (2018), Yang et al (2019).…”
mentioning
confidence: 99%
“…One review reported seven passive back exoskeletons (de Looze et al, 2016), and several designs have been published since then (Lamers et al, 2017;Baltrusch et al, 2020). Similarly, there have been many active back exoskeletons; some recent examples include Huysamen et al (2018), Ko et al (2018), Toxiri et al (2018), Yang et al (2019).…”
mentioning
confidence: 99%
“…In contrast to stiff devices, soft exoskeletons (also called exosuits) deliver mechanical power to the user using anchors that are typically made of clothing textiles and powered by cable-driven actuation (Awad et al, 2017;Schmidt et al, 2017;Li et al, 2018;Di Natali et al, 2019;Kim et al, 2019a,b;Xiloyannis et al, 2019;Yang et al, 2019;Goršič et al, 2021; Figure 3). Furthermore, soft exoskeletons are typically ergonomic, lightweight, and often designed following bioinspired techniques to better reproduce human physiological movements (Lessard et al, 2018;Figure 3b).…”
Section: Soft Exoskeleton Designsmentioning
confidence: 99%
“…This is especially critical for factory or industrial workers, or other individuals who do repetitive heavy lifting (Babicˇet al 2017;Lamers et al 2018). Several soft systems utilize passive methods of actuation such as pretensioned elastic bands or pulley systems that help support the back at opportune moments for injury (Cho et al 2017;Yang et al 2019). The benefit of actuation that uses tension in-line with the spine is the ability to store and release energy during lifting with the flexion and extension of the trunk.…”
Section: Back and Trunkmentioning
confidence: 99%